Pertanggungjawaban Pidana Terkait Kelalaian Pengobatan Tradisional Pada Suku Kemak di Kampung Sadi Kabupaten Belu Dalam Perspektif Hukum Positif Indonesia - Chatrine Aurora Bere Mau; Karolus K. Medan; Bhisa Vitus Wilhelmus (Asosiasi Peneliti dan Pengajar Ilmu Hukum Indonesia, 2025)
In Indonesia, traditional medicine has a legal position that is recognized and protected by state law in the provisions of article 50 paragraph (1) and paragraph (2) of Law Number 36 of 2009 concerning Health. It is also stated in the new Law Number 17 of 2023 concerning health article 192 paragraph (1). Although traditional medicine is recognized and regulated by national law, traditional medicine practitioners can also engage in malpractice acts. Currently, people have a lot of problems with traditional medicine, which is too prone to mishandling patients' diseases because of its methods that have not been clinically tested. The increasing number of cases of fracture infection caused by fracture shamans every year is one example of inappropriate handling that occurs in the Kemak Tribe in Kampung Sadi, Belu Regency. This research is a socio-legal research supported by an empirical approach that uses primary data and secondary data collected using interview and observation techniques and processed and dialysed using Editing, Coding, Verification, and Interpretation techniques. The results of this study show that (1) Negligence in traditional medicine is a serious problem that has a wide impact on individuals and society. (2) In traditional medicine, the prevention and control of negligence requires a comprehensive approach through education, regulation, and cooperation between the government, practitioners, and conventional health workers.